[Afisz. Incipit:] Państwowy Teatr "Wybrzeże" Repertuar 25.04-1.05.1949. (Gdańsk : [wydawca nieznany], 1949)
Afisz z repertuarem na 25.04-1.05.1949 r.
Keywords: Państwowy Teatr Wybrzeże (Gdańsk) -- druki ulotne